Innovation in Brazilian regulatory agencies: a study of successful experiences - Paula, Monaliza Ferreira Rodrigues de; Filgueira, Camila; Silva, Napie Galve Araújo (Revista de Administração da UFSM, 2022)
Objective: the study aims to expose the relationship between innovation and regulatory activities through the experiences of Brazilian regulatory agencies. Methodology: the study follows a bibliographical approach, adopting bibliographical and documentary research and collecting data from academic publications, reports and information published on the Federal Government’s website. Findings: through this essay it was possible to perceive how innovation is indispensable to regulatory activities, in view of the benefits provided to agencies and, especially, the positive impacts for society. Research limitations: since this is a theoretical study, the relationship between innovation and regulatory activities was limited to the experiences shared in the researched sources. Given a certain deficit of approach to the subject in the prevailing literature, we believe that an in loco research would be a more robust source of information and, thus, other innovation actions, not shared in academic works and/or websites, would be identified. Originality/value: the study’s contributions permeate the universe of the link between innovation and regulatory agencies, demonstrating the relevance of innovative actions to ensure efficiency and effectiveness in public services, taking four Brazilian agencies as an example. The absence of research on innovation in regulatory agencies at the national level characterizes the originality of the work. It is suggested, therefore, that regulatory agencies systematize their information on innovation actions and make it available to the public, in the form of a report, presenting the results achieved and the benefits acquired.